Android-Based Vehicle Collateral Storage Application at PT. Pegadaian (Persero) - Salomo Hasiolan Sidauruk; Ucuk Darusalam; Novi Dian Nathasia (Jurnal Mantik, 2021)
The development of technology in this era of globalization is growing quite rapidly, one of which is a multi-functional device that is often used today is a mobile application as a medium for accessing information easily. PT. Pegadaian (Persero) is a credit institution that distributes credit on a legal basis for pawning. In the pawnshop line, Pegadaian can receive gold, electronic, and vehicle pawn services. For vehicle pawning, the validation process based on the condition of the car is still done manually using a checklist document, therefore the application is made using the Android Studio programming language to digitize the vehicle pawn process at Pegadaian which is designed using the Software Development Life Cycle (SDLC) method.